Integration of Imam Al-Syathibi's Maqāṣid al-Syarī‘ah Concept in the Development of a Fair Islamic Economic Strategy - jannah, Rauza tul (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
Islamic economic thought developed from the efforts of scholars to integrate spiritual and moral values into economic activities in order to achieve the welfare of the people. This study aims to comprehensively examine the biography, scientific works, and economic thought patterns of Abu Ishaq Al-Syathibi within the framework of maqāṣid al-syarī‘ah. The research method used is a qualitative approach with a literature study through analysis of Al-Syathibi's main works, namely Al-Muwāfaqāt fī Uṣūl al-Syarī‘ah and Al-I‘tiṣām, as well as various relevant contemporary literature. The results of the study show that Al-Syathibi places economics as an integral part of the Islamic way of life, which is oriented towards benefit (jalb al-maṣlahah) and the prevention of harm (dar’ al-mafsadah). His thinking emphasizes a balance between spiritual and material aspects, social justice, and moral responsibility in the distribution of wealth. The concept of maqāṣid developed by Al-Syathibi became the ethical and philosophical basis for modern Islamic economics in facing the challenges of globalization and capitalism. Thus, Al-Syathibi's thoughts are relevant for building an adaptive, just, and welfare-oriented Islamic economic paradigm.